2011
DOI: 10.4038/cmj.v48i4.3328
|View full text |Cite
|
Sign up to set email alerts
|

Detection and management of alcohol misuse by general practitioners

Abstract: Introduction Alcohol misuse and related problems are common in Sri Lanka. The appropriateness of the primary care setting in dealing with alcohol misuse is well recognised, and general practitioners (GPs) constitute an important first contact setting.Methods One hundred and fifty randomly selected GPs practising in the Colombo and Gampaha districts were given a questionnaire to assess how they detect and manage alcohol misuse, and their attitudes towards persons who misuse alcohol.Results Seventy per cent of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…13 In another study conducted in Sri Lanka, the majority of GPs did not feel confident of their ability to detect (60%) or manage (55.2%) alcohol misuse. 18 In the PHC, the screening rate for HIV (75%, n=64), hepatitis B (65%, n=64) and hepatitis C (60.9%, n=64) was relatively similar to the Scottish study which indicated that GPs routinely provided screening for HIV (70.1%), hepatitis B (76.4%), and hepatitis C (70.1%). Regarding vaccination, Abu Dhabi FPs offered hepatitis B vaccination for 82.5% (n=57), a figure that was higher than for Scottish GPs (60.6%).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…13 In another study conducted in Sri Lanka, the majority of GPs did not feel confident of their ability to detect (60%) or manage (55.2%) alcohol misuse. 18 In the PHC, the screening rate for HIV (75%, n=64), hepatitis B (65%, n=64) and hepatitis C (60.9%, n=64) was relatively similar to the Scottish study which indicated that GPs routinely provided screening for HIV (70.1%), hepatitis B (76.4%), and hepatitis C (70.1%). Regarding vaccination, Abu Dhabi FPs offered hepatitis B vaccination for 82.5% (n=57), a figure that was higher than for Scottish GPs (60.6%).…”
Section: Discussionmentioning
confidence: 55%
“…13 In another study, 19.1% always referred the patient to a physician, 17% to a psychiatrist, and 13.3% to a centre dealing with alcohol related problems. 18 The most commonly seen substance misuse in Abu Dhabi was alcohol, followed by tramadol and benzodiazepine. Others included antihistamines, gabapentin, opiates, and artane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They should also receive an enhanced training in motivational techniques in order to improve the management of patients with substance misuse and to achieve harm minimisation goals [5]. The findings of Gurugama and colleagues highlight the urgency of these measures in our country [1].…”
Section: To the Editorsmentioning
confidence: 99%
“…I read the article on "Detection and management of alcohol misuse by general practitioners" [1] with concern. The impact of socially unacceptable behavioural patterns on family health and well being following substance misuse, particularly alcohol, is immense, and could impair happiness [2].…”
mentioning
confidence: 99%